Plasmodium vivax adherence to placental glycosaminoglycans. - Chotivanich, K; Udomsangpetch, R; Suwanarusk, R; Pukrittayakamee, S; Wilairatana, P; Beeson, J; Day, N; White, N (Public Library of Science, 2012)
BACKGROUND: Plasmodium vivax infections seldom kill directly but do cause indirect mortality by reducing birth weight and causing abortion. Cytoadherence and sequestration in the microvasculature are central to the pathogenesis of severe Plasmodium falciparum malaria, but the contribution of cytoadherence to pathology in other human malarias is less clear. METHODOLOGY: The adherence properties of P. vivax infected red blood cells (PvIRBC) were evaluated under static and flow conditions. PRINCIPAL FINDINGS: P. vivax isolates from 33 patients were studied. None adhered to immobilized CD36, ICAM-1, or thrombospondin, putative ligands for P. falciparum vascular cytoadherence, or umbilical vein endothelial cells, but all adhered to immobilized chondroitin sulphate A (CSA) and hyaluronic acid (HA), the receptors for adhesion of P. falciparum in the placenta. PvIRBC also adhered to fresh placental cells (N = 5). Pre-incubation with chondroitinase prevented PvIRBC adherence to CSA, and reduced binding to HA, whereas preincubation with hyaluronidase prevented adherence to HA, but did not reduce binding to CSA significantly. Pre-incubation of PvIRBC with soluble CSA and HA reduced binding to the immobilized receptors and prevented placental binding. PvIRBC adhesion was prevented by pre-incubation with trypsin, inhibited by heparin, and reduced by EGTA. Under laminar flow conditions the mean (SD) shear stress reducing maximum attachment by 50% was 0.06 (0.02) Pa but, having adhered, the PvIRBC could then resist detachment by stresses up to 5 Pa. At 37 °C adherence began approximately 16 hours after red cell invasion with maximal adherence at 30 hours. At 39 °C adherence began earlier and peaked at 24 hours. SIGNIFICANCE: Adherence of P. vivax-infected erythrocytes to glycosaminoglycans may contribute to the pathogenesis of vivax malaria and lead to intrauterine growth retardation.